Functional Role of Internal and External Visual Imagery: Preliminary Evidences from Pilates. (15th April 2018) - Montuori, Simone; Curcio, Giuseppe; Sorrentino, Pierpaolo; Belloni, Lidia; Sorrentino, Giuseppe; Foti, Francesca; Mandolesi, Laura
Abstract : The present study investigates whether a functional difference between the visualization of a sequence of movements in the perspective of the first- ( internal VMI-I) or third- ( external VMI-E) person exists, which might be relevant to promote learning. By using a mental chronometry experimental paradigm, we have compared the time or execution, imagination in the VMI-I perspective, and imagination in the VMI-E perspective of two kinds of Pilates exercises. The analysis was carried out in individuals with different levels of competence (expert, novice, and no-practice individuals). Our results showed that in the Expert group, in the VMI-I perspective, the imagination time was similar to the execution time, while in the VMI-E perspective, the imagination time was significantly lower than the execution time. An opposite pattern was found in the Novice group, in which the time of imagination was similar to that of execution only in the VMI-E perspective, while in the VMI-I perspective, the time of imagination was significantly lower than the time of execution. In the control group, the times of both modalities of imagination were significantly lower than the execution time for each exercise. The present data suggest that, while the VMI-I serves to train an already internalised gesture, the VMI-E perspective could be useful to learn, and then improve, the recently acquired sequence of movements. Moreover, visual imagery is not useful for individuals that lack a specific motor experience. The present data offer new insights in the application of mental training techniques, especially in field of sports. However, further investigations are needed to better understand the functional role of internal and external visual imagery.